Game Based Learning Assisted by Flash Card on Mastery of New Vocabulary of Indonesian Language - Ni Putu Chandra Maharani; Anak Agung Gede Agung; Maria Goreti Rini Kristiantari (International Journal of Elementary Education, 2026)
Low mastery of new vocabulary among elementary students has become a critical issue that affects their Indonesian language skills and overall learning outcomes. Conventional teaching approaches often fail to engage students actively, resulting in limited vocabulary acquisition and retention. This study aims to analyze the effect of a game-based learning model assisted by flash card media on students’ mastery of new vocabulary in Indonesian language learning. The research employed a quasi-experimental design using a non-equivalent pre-test post-test control group design. The population consisted of third-grade elementary students, with a total sample of 53 students selected through cluster random sampling. Data were collected using a written multiple-choice test designed to measure students’ vocabulary mastery before and after the intervention. The data were analyzed using inferential statistics through an independent sample t-test at a 5% significance level. The findings indicate that students who were taught using the game-based learning model assisted by flash cards demonstrated higher improvement in vocabulary mastery compared to those who received conventional instruction. This suggests that the integration of interactive learning strategies and visual media enhances student engagement and supports more effective vocabulary acquisition. In conclusion, the implementation of game-based learning assisted by flash cards contributes significantly to improving students’ mastery of new vocabulary and provides a meaningful and engaging learning experience.